Józef Patkowski at the Darmstadt International Summer Courses for New Music - Nowak, Marianne (Res Facta Nova, 2019)
Around 1960, the Darmstadt International Summer Courses for New Music were an important contact point for Polish composers and musicians to the Western avant-garde after years of isolation due to the doctrine of socialist realism imposed in Poland. During this first phase of Polish participation, Józef Patkowski participated twice in the Courses. Mainly based on sources to be found in the archives of the International Music Institute Darmstadt (IMD), this article di-scusses Patkowski’s perception of the Courses as well as his lecture on New Music in Poland which he held in Darmstadt 1962, and gives an insight into the organizational process of artistic contact between Poland and a Western festival.